A Recyclable Metal–Organic Framework as a Dual Detector and Adsorbent for Ammonia. Issue 55 (29th August 2017) - Gładysiak, Andrzej; Nguyen, Tu N.; Navarro, Jorge A. R.; Rosseinsky, Matthew J.; Stylianou, Kyriakos C.
Abstract: Recyclable materials for simultaneous detection and uptake of ammonia (NH3 ) are of great interest due to the hazardous nature of NH3 . The structural versatility and porous nature of metal–organic frameworks (MOFs) make them ideal candidates for NH3 capture. Herein, the synthesis of a water‐stable and porous 3‐dimensional Cu II ‐based MOF (SION‐10 ) displaying a ship‐in‐a‐bottle structure is reported; the pores of the hostSION‐10 framework accommodate mononuclear Cu II ‐complexes.SION‐10 spontaneously uptakes NH3 as a result of two concurrent mechanisms: chemisorption due to the presence of active Cu II sites and physisorption (bulk permanent porosity). The color of the material changes from green to blue upon NH3 capture, with the shifts of the UV/Vis absorption bands clearly seen at NH3 concentrations as low as 300 ppm.SION‐10 can be recovered upon immersion ofSION‐10⊃NH3 in water and can be further reused for NH3 capture for at least three cycles. Abstract : Response to Ammonia : A water stable and porous ship‐in‐a‐bottle structure (SION‐10 ), spontaneously uptakes NH3 and displays high sensitivity toward this hazardous gas. TheSION‐10⊃NH3 can be easily regenerated and recycled for at least three times.